(3eNJUQ ef cJGH GdCNdGb dLGdjfhSs
(3ChdgG (B:s
(3bGd GdNdb MGd ddfaS OGYjI GdEfSGf Edi Cf jaYd CaYGd GdfaS HGdCQhjI hdG ENJjGQ hHjGf Pdc Cf ef GdfGS bhekG EPG s
(3BNQgG (B:s
(3hGYde Cfg jfHZi Cf jLYd GdEfSGf MGdg heG gh Ydjg ajCSG Ydi ZjQg Je GdcJGH hGdeLO hGdTcQ ddg OGFekG CHOkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs